Circulating Osteonectin and Adipokine Profiles in Relation to Metabolically Healthy Obesity in Chinese Children: Findings From BCAMS. Issue 23 (4th December 2018) - Fu, Junling; Li, Yu; Esangbedo, Issy C.; Li, Ge; Feng, Dan; Li, Lujiao; Xu, Lu; Han, Lanwen; Li, Mingyao; Li, Changhong; Gao, Shan; Li, Ming; et al.
Abstract : Background: The role of adipokine dysregulation in determining the metabolic fate of obesity is not well studied. We aimed to examine whether the matricellular protein osteonectin and the profiles of certain adipokines could differentiate metabolically healthy obese (MHO) versus metabolically unhealthy obese phenotypes in childhood. Methods and Results: This study included 1137 obese children and 982 normal‐weight healthy (NWH) controls recruited from the BCAMS (Beijing Child and Adolescent Metabolic Syndrome) study. MHO was defined by the absence of insulin resistance and/or any metabolic syndrome components. Six adipokines—osteonectin, leptin, adiponectin, resistin, FGF21 (fibroblast growth factor 21), and RBP‐4 (retinol binding protein 4)—were assessed. Approximately 20% of obese children displayed the MHO phenotype. MHO children had a more favorable adipokine profile than metabolically unhealthy obese children, with lower osteonectin, leptin, and RBP‐4 and higher adiponectin (all P <0.05). Compared with normal‐weight healthy controls, MHO children displayed increased leptin, resistin, and RBP‐4 levels and reduced adiponectin concentrations (all P <0.05) but similar osteonectin and FGF21 levels. Among obese subjects, decreased osteonectin (odds ratio [OR]: 0.82; 95% confidence interval [CI] per standard deviation, 0.70–0.97), RBP‐4 (OR: 0.77; 95% CI per standard deviation, 0.64–0.93), and leptin/adiponectin ratio (OR: 0.58; 95% CI per standard deviation, 0.43–0.77) were independent predictors of MHO. In addition, compared with children without abnormalities, those with any 3 adipokine abnormalities were 80% less likely to exhibit the MHO phenotype (OR: 0.20; 95% CI, 0.10–0.43) and 3 times more likely to have metabolic syndrome (OR: 2.77; 95% CI, 1.52–5.03). Conclusions: These findings suggest that dysregulation of adipokines might govern the metabolic consequences of obesity in children. Low osteonectin levels, along with a healthy adipokine profile, might be used as an early marker of the MHO phenotype.